Sistem Integrasi dan Otomatisasi Tempat Sampah Cerdas Berbasis Internet of Things pada Tempat Sampah Publik - Brilyan Hendrasuryawan; Adkha Wildan Rizqia; Wisnu Widiarto; Ristu Saptono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to develop a Smart Waste Management System based on the Internet of Things integrated with an Android application to improve waste management effectiveness. The method used was system design and testing of a smart trash bin equipped with ultrasonic sensors and location detection to monitor bin conditions in real time. The results show that ultrasonic sensor 1 and ultrasonic sensor 2, system testing, and system integration testing functioned as expected with a low error rate. The integration testing as the main evaluation point achieved an accuracy value of 99.7%. In conclusion, the developed system is able to assist sanitation workers in tracking and collecting waste more effectively and efficiently. Keywords: Android application, Internet of Things, smart trash bin, waste management